Corrosion Behavior of E690 Steel in Tropical Marine Atmospheres Based on Electrochemical Noise Technique - Peichang DENG; Junhao ZENG; Jiezhen HU; Baoyu GENG; Junhao DENG; Wenjie LAN (Electrochemistry)
In the tropical marine atmospheric environment of Zhanjiang, E690 steel was subjected to 7-, 15-, 30-, 90-, 180-, 270-, and 360-day exposure experiments. Electrochemical noise (EN) technology, combined with the weight loss method, corrosion morphology observation, X-ray diffraction analysis (XRD) and polarization curve testing, was used to study the corrosion behavior of E690 steel in a tropical marine atmospheric environment. The results showed that during the initial exposure period, the voltage and current noise fluctuation amplitudes of the EN electrode were large, the current standard deviation (SI) and white noise level (W) were large, the corrosion current density was high, and the corrosion rate of E690 steel was high, mainly due to the small amount of corrosion products on the surface of the sample. Moreover, the voltage and current noise exhibited a nearly symmetrical distribution on both sides of the average value, accompanied by many transient peaks, indicating uniform corrosion of E690 steel. As the exposure time increased, the amplitude of the voltage and current noise fluctuations decreased, the current standard deviation (SI) and white noise level (W) gradually decreased, the corrosion current density decreased, and the corrosion rate decreased and tended to stabilize. In the later stage of exposure to sunlight, pitting corrosion appeared on the surface of E690 steel, and the voltage noise exhibited high-frequency vibration without obvious transient peak characteristics. The current noise also showed high-frequency vibration, and the number of transient peaks significantly decreased. The corrosion type of E690 steel changed from uniform corrosion to pitting corrosion.